Sexual health practices of 16 to 19 year olds in New Zealand: an exploratory study - Robyn Aitken; Sonja J. Ellis (CSIRO Publishing, 2020)
ABSTRACT INTRODUCTIONNew Zealand sexual health surveillance data suggest that young people aged 15-19 years are at considerable risk of contracting sexually transmitted infections. Although there is an established body of international research around sexual behaviours and sexual health practices among teenagers, there is a dearth of local research focusing on this age group. AIMThe aim of this study was to explore the sexual repertoires and sexual health practices among teenagers in New Zealand with a view to better understanding levels of risk in this age group. METHODSThis study comprised a cross-sectional online survey designed to ask questions about sexual behaviours. A convenience sample of young people (n=52) aged 16-19 years living in New Zealand completed the survey. RESULTSMost participants (71.2%) were sexually active, reporting engagement in a range of sexual practices. The most commonly reported sexual behaviours were penis-in-vagina sex (86.5%) and oral sex with a person-with-a-penis (81.1%). Infrequent and inconsistent use of barrier protection across all types of sexual behaviour was also reported. DISCUSSIONThe findings of this study highlight the importance of ensuring that young people have access to sexual health education that routinely includes health information and advice addressing the full range of sexual practices, regardless of the identity classifications they may use, or that may be attributed to them.